RELATIONSHIP OF THINKING AND IMAGINATION PROCESSES WITH SPEECH ACTIVITY (Multidisciplinary Journal of Science and Technology, 2024)
In recent years, many studies have begun to appear in world psychology and linguistics on issues of the psyche, language, and speech activity. Because the bulk of information reaches human consciousness through the linguistic direction. The article describes the relationship between the processes of thinking and imagination in the field of psycholinguistics and speech activity. And their research is expressed based on scientific sources. It studies language and perception, thinking, and the “nature of language.” In the real mental activity of a person, a mental process, state or characteristic of a person is manifested.